Aportaciones a la historiografía de lo social desde el Instituto de Historia Social Valentín de Foronda de la UPV/EHU - Ruzafa Ortega, Rafael (Huarte de San Juan. Geografía e Historia, 2015)
This article reviews the historiographical work on social history developed by the members of the Instituto de Historia Social Valentín de Foronda since 1980. Focuses, among other relevant points of view, in the power relationships, the making and consolidation of the working class and the forms of rural world adaptation to modernity.
Keywords: Basque Country; social history; workers; rural world